2023 Bangladesh Rheumatology Society (BRS) Rheumatoid Arthritis Management Recommendations: What is new? - Majumder, Muhammad Shoaib Momen; Hasan, A T M Tanveer; Choudhury, Minhaj Rahim; Miah, Md Titu; Amin, Md Robed; Shahin, Abu; Haq, Syed Atiqul (Bangladesh Journal of Medicine, 2024)
Rheumatoid arthritis (RA) is the most common inflammatory polyarthritis in Bangladesh. The management recommendations for patients with rheumatoid arthritis (RA) is the first initiative in Bangladesh by the Bangladesh Rheumatology Society (BRS) and an updated contribution following a paradigm shift in the management of RA. These recommendations encompass the most crucial elements in treating rheumatoid arthritis, particularly in a country where infection, including tuberculosis, is prevalent, but the resources are limited. BRS established a task force (TF) consisting of four rheumatologists. The task group conducted a comprehensive search for all relevant literature, including the latest ACR, EULAR, APLAR, and other guidelines and systematic literature reviews up until October 2023. A steering committee was established, comprising rheumatologists and internists. We adhered to the EULAR standard operating procedures for classifying levels of evidence and assigning grades to recommendations. This recommendation consists of two components: a general section that includes the diagnosis of rheumatoid arthritis, the nomenclature of disease-modifying antirheumatic drugs (DMARDs), and disease activity indexes; and a therapy section. The task team reached a consensus on four fundamental principles and twelve recommendations. Overarching themes encompass the identification of diseases at an early stage and the ongoing monitoring of disease activity. Recommendations 1-5 propose the utilization of glucocorticoids, NSAIDs, and conventional synthetic DMARDs (csDMARD) as treatment options. Recommendations 6-9 expand the utilization of targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs) and biological diseasemodifying antirheumatic drugs (bDMARDs). The recommended treatment for rheumatoid arthritis involves starting with methotrexate (MTX) or another conventional synthetic disease-modifying antirheumatic drug (csDMARD) if MTX is not suitable. This is done in the initial phase. A targeted synthetic DMARD (tsDMARD) is added in the second phase. In later phases, moving to a different tsDMARD or a biologic DMARD (bDMARD) may be necessary. Recommendations 10-12 pertain to the screening of infections, administration of vaccines, and the gradual reduction of disease-modifying antirheumatic drugs (DMARDs). Due to the cost-benefit analysis, BRS has suggested using targeted synthetic disease-modifying antirheumatic medicines (tsDMARDs) in the second phase and biologics in the third phase. The use of the Padua Prediction Score is advised to evaluate the likelihood of vascular thromboembolism in persons who are taking or undergoing dose escalation of tsDMARDs. Bangladesh has a higher prevalence of RA. This recommendation will serve as a tool to treat this high burden of patients with RA scientifically and more effectively. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 153